A selected reaction monitoring‐based analysis of acute phase proteins in interstitial fluids from experimental equine wounds healing by secondary intention. Issue 3 (31st March 2016) - Bundgaard, Louise; Bendixen, Emøke; Sørensen, Mette Aa.; Harman, Victoria M.; Beynon, Robert J.; Petersen, Lars J.; Jacobsen, Stine
Abstract: In horses, pathological healing with formation of exuberant granulation tissue (EGT) is a particular problem in limb wounds, whereas body wounds tend to heal without complications. Chronic inflammation has been proposed to be central to the pathogenesis of EGT. This study aimed to investigate levels of inflammatory acute phase proteins (APPs) in interstitial fluid from wounds in horses. A novel approach for absolute quantification of proteins, selected reaction monitoring (SRM)‐based mass spectrometry in combination with a quantification concatamer (QconCAT), was used for the quantification of five established equine APPs (fibrinogen, serum amyloid A, ceruloplasmin, haptoglobin, and plasminogen) and three proposed equine APPs (prothrombin, α‐2‐macroglobulin, and α‐1‐antitrypsin). Wound interstitial fluid was recovered by large pore microdialysis from experimental body and limb wounds from five horses at days 1, 2, 7, and 14 after wounding and healing without (body) and with (limb) the formation of EGT. The QconCAT included proteotypic peptides representing each of the protein targets and was used to direct the design of a gene, which was expressed in Escherichia coli in a media supplemented with stable isotopes for metabolically labeling of standard peptides. Co‐analysis of wound interstitial fluid samples with the stable isotope‐labeled QconCAT tryptic peptides in known amounts enabled quantification of the APPs in absolute terms. The concentrations of fibrinogen, haptoglobin, ceruloplasmin, prothrombin, and α‐1‐antitrypsin in dialysate from limb wounds were significantly higher than in dialysate from body wounds. This is the first report of simultaneous analysis of a panel of APPs using the QconCAT‐SRM technology. The microdialysis technique in combination with the QconCAT‐SRM‐based approach proved useful for quantification of the investigated proteins in the wound interstitial fluid, and the results indicated that there is a state of sustained inflammation in equine wounds healing with formation of EGT.